Determinan Pengangguran Terselubung di Sumatera Barat - Hidayat, Alvin; Joan Marta (Media Riset Ekonomi Pembangunan (MedREP), 2025)
Since the 1998 monetary crisis, Indonesia's economy has grown positively, but This study aims to determine and analyze the impact of disguised unemployment determinants in West Sumatra. The study secondary data sourced from the National Economic Survey (SAKERNAS) issued by the Central Statistic Agency (BPS). With variables grouped into two parts, namely the dependent variable wich in this study uses disguised unemployment and the independent variables of education, employment, age, work experience and gender. This study is descriptive ang inductive, this study uses logistic regression anlysis with a cross section in 2020 in West Sumatra. The resultd of study show thet education, employment, age, work experience and gender have a positive and significant effect on disguised unemployment in West Sumatra.